A Comprehensive Review of Fast Charging Infrastructure for Electric Vehicles. Issue 3 (3rd July 2018) - Khan, Wajahat; Ahmad, Aqueel; Ahmad, Furkan; Saad Alam, Mohammad
Abstract: The idea of electrified transportation is envisioned to be a promising approach to alleviate the issue of climate change. However, a cost-effective commercialization and wide acceptance of electrified transportation necessitates the development of an economical, reliable, and fast charging infrastructure. The incorporation of a well-defined electric vehicle (EV) fast charging infrastructure in the smart grid can offer numerous potential opportunities, particularly from the perspective of vehicle to grid (V2G) technology as well as a solution to the renewable energy intermittency issue. This work reviews the state-of-the-art technology for fast charging of electric vehicles with a comprehensive coverage of the research work done related to the challenges and road blocks to be encountered in its implementation. A comparison of conductive and inductive charging systems is presented followed by an overview of the charging standards and a discussion on the topologies presented in the literature for fast charging stations. A detailed account is presented concerning the issues and opportunities on integration of fast charging infrastructure with grid. The economic aspects of fast charging infrastructure along with an overview of prospective areas for future research in this field are also presented. Abstract :